R package to estimate intracluster correlation coefficient with confidence interval for binary data. (March 2018) - Chakraborty, Hrishikesh; Hossain, Akhtar
Abstract: Background and Objective: The Intracluster Correlation Coefficient (ICC) is a major parameter of interest in cluster randomized trials that measures the degree to which responses within the same cluster are correlated. There are several types of ICC estimators and its confidence intervals (CI) suggested in the literature for binary data. Studies have compared relative weaknesses and advantages of ICC estimators as well as its CI for binary data and suggested situations where one is advantageous in practical research. The commonly used statistical computing systems currently facilitate estimation of only a very few variants of ICC and its CI. To address the limitations of current statistical packages, we developed an R package, ICCbin, to facilitate estimating ICC and its CI for binary responses using different methods. Methods: TheICCbin package is designed to provide estimates of ICC in 16 different ways including analysis of variance methods, moments based estimation, direct probabilistic methods, correlation based estimation, and resampling method. CI of ICC is estimated using 5 different methods. It also generates cluster binary data using exchangeable correlation structure. Results: ICCbin package provides two functions for users. The functionrcbin() generates cluster binary data and the functioniccbin() estimates ICC and it's CI. The users can choose appropriate ICC and its CI estimate from the wide selection of estimates from the outputs. Conclusions: TheR packageICCbin presents very flexible and easy to use ways to generate cluster binary data and to estimate ICC and it's CI for binary response using different methods. The packageICCbin is freely available for use withR from the CRAN repository (https://cran.r-project.org/package=ICCbin ). We believe that this package can be a very useful tool for researchers to design cluster randomized trials with binary outcome.